2011
DOI: 10.1007/s11596-011-0391-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between distribution of Helicobacter Pylori in oral cavity and chronic stomach conditions

Abstract: In this study, the colonization and distribution of Helicobacter pylori (Hp) in patients with chronic gastric diseases were investigated and the relationship between the periodontal initial treatment and presence of Hp in oral cavity was examined to better understand the connection between Hp infection and chronic diseases. Primers for PCR amplification were designed according to ureC gene and cagA genes of Hp. Specimens were harvested from different sites of 96 patients with chronic gastric diseases and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 15 publications
2
38
1
Order By: Relevance
“…28, 29, 30, 31, 32, 33 Adding periodontal treatment to standard triple antibiotic therapy also increased the effectiveness of gastric H. pylori eradication in studies of a general population cohort and of patients with chronic gastric illness. 34, 35 However, periodontal disease's association with gastric and duodenal ulcer may be related to mechanisms other than H. pylori colonization, as our data showed similar associations between periodontal disease and risk of H. pylori -positive and H. pylori -negative ulcers. One hypothesis is that oral microbiota, which have been associated with the impaired healing of periodontal lesions, 36, 37, 38, 39 may also be a source of chronic inflammation and impaired wound healing of gastrointestinal tract mucosa.…”
Section: Discussionsupporting
confidence: 53%
“…28, 29, 30, 31, 32, 33 Adding periodontal treatment to standard triple antibiotic therapy also increased the effectiveness of gastric H. pylori eradication in studies of a general population cohort and of patients with chronic gastric illness. 34, 35 However, periodontal disease's association with gastric and duodenal ulcer may be related to mechanisms other than H. pylori colonization, as our data showed similar associations between periodontal disease and risk of H. pylori -positive and H. pylori -negative ulcers. One hypothesis is that oral microbiota, which have been associated with the impaired healing of periodontal lesions, 36, 37, 38, 39 may also be a source of chronic inflammation and impaired wound healing of gastrointestinal tract mucosa.…”
Section: Discussionsupporting
confidence: 53%
“…Gao et al determined the effect of triple therapy (systemic therapy) and triple therapy combined with oral treatment, on the eradication rate of gastric H. pylori. 15 Combination therapy proved to be more effective, as one year after the end of treatment the incidence of these bacteria was twice as low (32.4%) as compared to the exclusive use of systemic therapy (62.8%). A similar relationship, showing an increased degree of H. pylori eradication after combination therapy, has been demonstrated in the meta-analyzes of Ren et al 56 and Bouziane et al 57 It was found that the relative chance of gastric H. pylori recurrence in patients who underwent oral and gastric therapy was reduced by 63%.…”
Section: Infl Uence Of Oral H Pylori On Gastric Infections and Eradimentioning
confidence: 96%
“…Other regions include the tonsils and dorsal mucosa of the tongue. 15,37 Many studies based on genetic or serological tests in H. pylori detection have shown the presence of this bacterium in the oral cavity or stomach, while the number of studies demonstrating the effective isolation of this microbe from the oral environment is still very low. Hirsch et al 23 successfully managed to isolate live H. pylori from samples taken from dental canals.…”
Section: Epidemiology Of Oral H Pylori Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of these data suggests that periodontal treatment in combination with systemic therapy could be a promising approach to increase the efficacy of the treatment and to decrease the risk of infection recurrence (10). Based on the literature data and on our experience we recommend:…”
Section: Treatment Protocolmentioning
confidence: 99%